Evidence for a role of Sky1p-mediated phosphorylation in 3′ splice site recognition involving both Prp8 and Prp17/Slu4 - DAGHER, SUE F.; FU, XIANG-DONG (RNA (Cambridge), 2001)
The SRPK family of kinases is specific for RS domain-containing splicing factors and known to play a critical role in protein–protein interaction and intracellular distribution of their substrates in both yeast and mammalian cells. However, the function of these kinases in pre-mRNA splicing remains unclear. Here we report that SKY1, a SRPK family member in Saccharomyces cerevisiae, genetically interacts with PRP8 and PRP17/SLU4, both of which are involved in splice site selection during pre-mRNA splicing. Prp8 is essential for splicing and is known to interact with both 5′ and 3′ splice sites in the spliceosomal catalytic center, whereas Prp17/Slu4 is nonessential and is required only for efficient recognition of the 3′ splice site. Interestingly, deletion of SKY1 was synthetically lethal with all prp17 mutants tested, but only with specific prp8 alleles in a domain implicated in governing fidelity of 3′AG recognition. Indeed, deletion of SKY1 specifically suppressed 3′AG mutations in ACT1-CUP1 splicing reporters. These results suggest for the first time that 3′AG recognition may be subject to phosphorylation regulation by Sky1p during pre-mRNA splicing.